CPW-Fed Slot-Like Sleeve-Monopole Antenna with Bandwidth Enhancement for UWB Wireless Communications - Bashiri, S.; Ghobadi, Ch.; Nourinia, J.; Ojaroudi, M. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper proposes a novel slot-like sleeve-monopole antenna for ultra wideband applications with multi-resonances performance. The antenna consists of a CPW-fed sleeve monopole antenna with a coupled inverted Ushaped strip, surrounded by a pair of folded strips, which provides a wide usable fractional bandwidth of more than 120 % (3.09 GHz - 12.86 GHz). By adding a coupled inverted U-shaped strip with variable dimensions on the radiating patch and also by inserting two folded strips, additional resonances are excited and hence much wider impedance bandwidth can be produced, especially at the higher band. The designed antenna has a small size of 30 × 30 mm2 . Simulated and experimental results obtained for this antenna show that it exhibits good radiation behavior within the UWB frequency range.